Acute Bilateral Ischemic Stroke in a Young Adult without risk factors (Translation: The University of Toledo Journal of Medical Sciences, 2019)
Cerebrovascular accidents (CVA) remain a leading cause of death as well as a major burden from both a quality of life and disability standpoint.1,2 This is particularly problematic for younger CVA patients who may be disabled during their most productive years of life.2,3 Although CVAs in younger patients are rare, incidence of CVAs among young adults continues to remain stable and these patients often present atypically, such as with headache and dizziness, highlighting a persistent concern for care providers.4-7 Furthermore, CVAs may be misdiagnosed as seizures and the sequelae of CVAs may themselves precipitate traumatic accidents, further obscuring assessment. These difficulties complicate differential diagnoses and result in the potential for misdiagnosis and delayed time-sensitive CVA treatment.5,8 We describe a case of a healthy young patient presenting to the ED initially as a trauma resuscitation and subsequently converting to a stroke resuscitation outside the window for tPA treatment.
Keywords: young stroke; bilateral CVA; thrombectomy; postpartum